Anemia in children with chronic renal failure Special attention erythrocyte indices and iron deficiency anemia - Adi Suryanto B; Partini P Trihono; Agus Firmansyah (Indonesian Pediatric Society, 2006)
Background Anemia in chronic renal failure (CRF) has beenproved to influence the quality of life, increasing morbidity andmortality. Early diagnosis and prompt treatments of anemia aremandatory to manage CRF appopriately. So far data of anemia inCRF in Indonesia is limited.Objective To find out the profile of anemia in children with CRF atCipto Mangunkusumo Hospital (CMH), Jakarta, with special atten-tion in erythrocyte indices and iron deficiency anemia.Methods Cross-sectional descriptive study was carried out onpatients with CRF and anemia in CMH since October 2003 to April2004.Results There were 20 CRF patients, aged between 1 year 3 month-15 year old, mostly were above 10 year old, 11 patients were malesand 9 were females. The most frequent etiologies were urinarytract infection (UTI) in 10 cases and nephrotic syndrome in 6 cases.Of those 20 patients, 14 suffered from anemia with erythrocyteindices, normochrome normocytic in 9 patients and hypochromemicrocytic in 5 patients. Of 14 anemic patients only 1 patient suf-fered from iron deficiency anemia of less than 10 mg/l and transferinsaturation of less than 12%. Based on serum iron (SI) concentra-tion only, 7 patients were diagnosed as having iron deficiency ane-mia.Conclusion Most patients with chronic renal failure havenormochrome normocytic anemia. Hypochromic microcytic irondeficiency anemia is scarcely found in this group of patients.